2015
DOI: 10.1186/s13567-015-0230-z
|View full text |Cite
|
Sign up to set email alerts
|

Eimeria bovis infection modulates endothelial host cell cholesterol metabolism for successful replication

Abstract: During first merogony Eimeria bovis forms large macromeronts in endothelial host cells containing >120 000 merozoites I. During multiplication, large amounts of cholesterol are indispensable for the enormous offspring membrane production. Cholesterol auxotrophy was proven for other apicomplexan parasites. Consequently they scavenge cholesterol from their host cell apparently in a parasite-specific manner. We here analyzed the influence of E. bovis infection on endothelial host cell cholesterol metabolism and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 58 publications
(92 reference statements)
5
40
1
Order By: Relevance
“…A similar feature has also been suggested for the pathogenic species E. bovis and E. zuernii (Kawahara et al, 2010). It is intriguing to verify that despite the different host The phylogenetic proximity of E. arloingi and E. bovis may be in accordance with other common features of parasite-host cell interactions, such as the modulation of host cell-apoptosis (Lang et al, 2009), -cytoskeleton (Hermosilla et al, 2008) and -metabolism (Hamid et al, 2014;Hamid et al, 2015;Silva et al, 2015;Taubert et al, 2010) to guarantee successful macromeront formation.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…A similar feature has also been suggested for the pathogenic species E. bovis and E. zuernii (Kawahara et al, 2010). It is intriguing to verify that despite the different host The phylogenetic proximity of E. arloingi and E. bovis may be in accordance with other common features of parasite-host cell interactions, such as the modulation of host cell-apoptosis (Lang et al, 2009), -cytoskeleton (Hermosilla et al, 2008) and -metabolism (Hamid et al, 2014;Hamid et al, 2015;Silva et al, 2015;Taubert et al, 2010) to guarantee successful macromeront formation.…”
Section: Discussionsupporting
confidence: 61%
“…For example, E. bovis depends on the host endothelial cell supply of energy and cellular building blocks for its massive offspring formation (Hamid et al, 2014;Hamid et al, 2015). Most notably for cholesterol and given that apicomplexan protozoa are considered as defective in de novo cholesterol biosynthesis (Coppens et al, 2000;Ehrenman et al, 2013;Taubert et al, 2010), this parasite appears to scavenge cholesterol via different pathways during macromeront formation (Hamid et al, 2015) for successful replication. Additionally, the downregulation of early host endothelial cell immune reactions in presence of E. arloingi (Silva et al, 2015), E. bovis (Taubert et al, 2006;Taubert et al, 2010) and also E. ninakohlyakimovae (Perez et al, 2015) was reported.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this outcome has been corroborated by studies using isotope‐resolved metabolomics, where amastigotes exhibited a glucose‐sparing metabolism associated with increased rates of beta‐oxidation (Saunders et al., ). Thus, these data together with the rising significance of endocytically low‐density lipoprotein (LDL)‐derived cholesterol during parasitic infections (Bansal, Bhatti, & Sehgal, ; Hamid et al., ; Johndrow, Nelson, Tanowitz, Weiss, & Nagajyothi, ) prompted our interest in lipid trafficking and metabolism in the host cell, and in the Leishmania ‐containing PV in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these data together with the rising significance of endocytically low-density lipoprotein (LDL)-derived cholesterol during parasitic infections (Bansal, Bhatti, & Sehgal, 2005;Hamid et al, 2015;Johndrow, Nelson, Tanowitz, Weiss, & Nagajyothi, 2014) prompted our interest in lipid trafficking and metabolism in the host cell, and in the Leishmaniacontaining PV in particular.…”
Section: Introductionmentioning
confidence: 99%
“…LDLR-A proteins are crucial in receptor-mediated endocytosis of ligands, particularly cholesterol and acyglycerols. Many parasites are unable to produce cholesterol and are, therefore, dependent on host acquisition to fuel cell proliferation and differentiation 46,50 . Consequent alterations in host cholesterol homeostasis can lead to immune dysregulation and disease pathology.…”
Section: Host-specific Transcription Indicates Specialisation In Nutrmentioning
confidence: 99%